DEVELOPMENT OF A COMPLEX PLANT-BASED REMEDY FOR USE IN DENTISTRY (International journal of artificial intelligence, 2024)
Dentistry is one of the rapidly evolving fields, continuously requiring innovations aimed at improving patient care and minimizing side effects. Recently, plant-based complex remedies have been gaining popularity as alternatives to chemical drugs. The abundance of active compounds in natural plants makes them highly effective in treating dental issues such as dental caries, periodontitis, stomatitis, gingivitis, and other oral cavity conditions.